(3HdZI GdhGLO aj JQLeI TjN GdESdGe GdhGdOs - (3GdnZpqRj GdYGeQj GdbQTj GdOeTbqj, CHh GdecGQe, fLe GdOjf, eMeO Hf eMeO Hf eMeO, (B1061 (3g`s
(3ChdgG (B:s
(3GdMGaX CHj LYaQ CMeO Hf EHQGgje Hf GdRjf GdKbaj GdYGUej , bGd GHf GdeQGHW SeGYG bGd CNHQfG GdMGaX CHh GdMSf Ydj Hf eMeO Hf jMji GdZGabj YQa HGdSGQj CNHQfG Hg GdMGaX CHh eMeO GdMLQjs
(3BNQgG (B:s
(3jbhd GdCQPdhf Hfh bTjQ WhGd GdOgQ dG JfSi YdjG (B- (3CMH eMeOG MHG TOjOG hYHGSG hMeRI hGdhUjG (B- (3aEf jcf MHge QTOG CUHg hdjS HeNWF Ef cGf ZjG (B(( (3cPG (B)s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7 / 63s
(3eYLe GdeDdajf (B3 / 685s
(3EjVGM Gdecfhf (B1 / 194s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdMOjK hGdeUWdMs